Seroprevalence of Hepatitis C, Hepatitis B, Cytomegalovirus, and Human Immunodeficiency Viruses in Multitransfused Thalassemic Children in Upper Egypt - Ramadan A. Mahmoud; Abdel-Azeem M. El-Mazary; Ashraf Khodeary (Advances in Hematology)
Background. Frequent blood transfusions in thalassemia major children expose them to the risk of transfusion-transmitted infections (TTIs). The aim of this study was to estimate the prevalence of hepatitis C virus (HCV), hepatitis B virus (HBV), human immunodeficiency virus (HIV), and cytomegalovirus (CMV) in thalassemic children attending the Pediatrics Departments of both Sohag and Minia Universities of Upper Egypt, during the period from May 2014 to May 2015. Methods. Serum samples were screened for hepatitis B surface antigen (HBsAg), anti-HCV, anti-CMV, and anti-HIV type 1 and type 2 using the Vitek Immunodiagnostic Assay System. Results. The frequencies of anti-HCV, HBsAg, anti-CMV, and anti-HIV type 1 and type 2 were found to be 37.11%, 4.12%, 4.12%, 0.00%, and 0.00%, respectively. Seropositivity for anti-HCV, HBsAg, and anti-CMV increased with increasing age of the patients, duration of the disease, serum ferritin level (ng/mL), and liver enzymes (U/L), while it was not significantly associated with gender, frequency of blood transfusion, or the status of splenectomy operation (P>0.05). Conclusion. The frequency of TTIs, especially HCV, is considerably high among Egyptian children with thalassemia major. It is therefore important to implement measures to improve blood transfusion screening, such as polymerase chain reaction, in order to reduce TTIs from blood donor units.